2020
DOI: 10.1101/2020.05.30.125583
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Pharmacogenetics at scale: An analysis of the UK Biobank

Abstract: Pharmacogenentics (PGx) studies the influence of genetic variation on drug response. Clinically actionable associations inform guidelines created by the Clinical Pharmacogenetics Implementation Consortium (CPIC), but the broad impact of genetic variation on entire populations is not well-understood. We analyzed PGx allele and phenotype frequencies for 487,409 participants in the U.K. Biobank, the largest PGx study to date. For fourteen CPIC pharmacogenes known to influence human drug response, we find that 99.… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1

Relationship

5
4

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 39 publications
3
26
0
Order By: Relevance
“…We investigated drug-gene relationships for nine important pharmacogenes in the UK Biobank for 222,114 participants using primary care data from the National Health System, provided by the UK Biobank 10 . The pharmacogenetic alleles used in this study were derived from a previously reported procedure, described here in brief 8 . The genetic data used in this study was imputed from the Axiom Biobank Array for each participant.…”
Section: Pharmacogenetic Allele Callingmentioning
confidence: 99%
See 1 more Smart Citation
“…We investigated drug-gene relationships for nine important pharmacogenes in the UK Biobank for 222,114 participants using primary care data from the National Health System, provided by the UK Biobank 10 . The pharmacogenetic alleles used in this study were derived from a previously reported procedure, described here in brief 8 . The genetic data used in this study was imputed from the Axiom Biobank Array for each participant.…”
Section: Pharmacogenetic Allele Callingmentioning
confidence: 99%
“…Biobanks offer an opportunity to retrospectively assess known drug-gene relationships in a clinical setting as well as offer the opportunity to discover new drug-gene associations. Biobanks and electronic health records have been used to perform targeted association studies between genomics and response to individual drugs 7 as well as characterize frequency of pharmacogenetic alleles in populations 8,9 , but studies of drug response across a large number of drugs have not yet been performed.…”
Section: Introductionmentioning
confidence: 99%
“…These variants can affect the metabolism, transport and action of drugs throughout the body and may influence efficacy or lead to adverse events. Studies have shown as many as 99.8% of individuals carry at least one genetic variant that could lead to adverse outcomes for at least one drug [6][7][8] . In the past, clinical practice overlooked the influence of genetics on drug response, and-except for several extreme cases 9 -used a standardized dose of any particular drug for most patients, with some trial-and-adjustment to determine the ideal drug and dosage.…”
Section: Pgx and Iem In Current Clinical Practicementioning
confidence: 99%
“…The current reliance on manual curation for scoring of CYP2D6 haplotypes limits the ultimate utility of CYP2D6 phenotype prediction for pharmacogenetic guidance of treatment decisions. It is estimated that individuals carrying CYP2D6 haplotypes with an unknown, uncertain, or uncurated function (herein referred to collectively as uncurated) range from 2 to 9%, with a study of the UK Biobank finding that 3.4% of individuals carry haplotypes that cannot be mapped to a predefined function[ 22 , 23 ]. Individuals carrying a haplotype with uncurated function cannot be assigned to a distinct metabolizer group using the AS and are instead labeled as “Indeterminate”.…”
Section: Introductionmentioning
confidence: 99%